FINITE ELEMENT ANALYSIS OF CYCLIC PROPERTY AND FATIGUE LIFE PREDICTION FOR 316L STAINLESS STEEL - TAN JingYing; LI JiangHua; SHAO Ning; JIN Dan (Jixie qiangdu)
Low cycle fatigue tests were carried for 316 L stainless steel and the material cyclic property was simulated by finite element method. The test results show that the significant cyclic additional hardening can be observed in different strain ranges and it is more evident with increase in strain range. The mixing model combined with the nonlinear kinematic hardening and the isotropic hardening is used to describe the elastic and plastic behavior. The simulation results of stress-strain agree well with the test results for the second cycle in different strain ranges. The error of the maximum stress for first 20 cycles between the simulation results and test results depends on the strain range and the maximum error is 3. 20%. The energy approach is used to predict the fatigue life based on the test results and simulation results and the prediction results are in a factor-2 scatter band.